2023
DOI: 10.1177/08968608231209849
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between number of daily exchanges at CAPD start with clinical outcomes

Luca Nardelli,
Antonio Scalamogna,
Elisa Cicero
et al.

Abstract: Background: Peritoneal dialysis (PD) continues to be demanding for patients affected by kidney failure. In kidney failure patients with residual kidney function, the employment of incremental PD, a less onerous dialytic prescription, could translate into a decrease burden on both health systems and patients. Methods: Between 1st January 2009 and 31st December 2021, 182 patients who started continuous ambulatory peritoneal dialysis (CAPD) at our institution were included in the study. The CAPD population was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Secondly, the severity of peritonitis could not be assessed and analysed with the use of electronic data. Thirdly, a recent study showed that the number of daily manual exchanges in CAPD was associated with the risk of peritonitis [ 14 ] but these data could not be incorporated into the current analysis. A different study design is warranted to further explore the effect of the incremental approach in CAPD compared with APD.…”
mentioning
confidence: 99%
“…Secondly, the severity of peritonitis could not be assessed and analysed with the use of electronic data. Thirdly, a recent study showed that the number of daily manual exchanges in CAPD was associated with the risk of peritonitis [ 14 ] but these data could not be incorporated into the current analysis. A different study design is warranted to further explore the effect of the incremental approach in CAPD compared with APD.…”
mentioning
confidence: 99%